167k views
0 votes
Solve using substitution methody= -5x + 2y= -10x + 7

User Jahu
by
4.8k points

1 Answer

4 votes

ANSWER

(1, -3)

Step-by-step explanation

Since we have y in function of x in both equations, we can replace the first equation into the second and solve for x:


\begin{gathered} -5x+2=-10x+7 \\ -5x+10x=7-2 \\ 5x=5 \\ x=1 \end{gathered}

And then replace x = 1 into one of the equations to find the value of y:


\begin{gathered} y=-5x+2 \\ y=-5\cdot1+2 \\ y=-5+2 \\ y=-3 \end{gathered}

The solution is (1, -3)

User Xnakos
by
5.8k points